2013
DOI: 10.1523/jneurosci.0404-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Orientation Selectivity in the Mammalian Visual Pathway

Abstract: Orientation selectivity is a property of mammalian primary visual cortex (V1) neurons, yet its emergence along the visual pathway varies across species. In carnivores and primates, elongated receptive fields first appear in V1, whereas in lagomorphs such receptive fields emerge earlier, in the retina. Here we examine the mouse visual pathway and reveal the existence of orientation selectivity in lateral geniculate nucleus (LGN) relay cells. Cortical inactivation does not reduce this orientation selectivity, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(139 citation statements)
references
References 81 publications
8
112
3
1
Order By: Relevance
“…Given that it occurs in the mouse, SRP offers an opportunity for interventional experimental approaches to test this hypothesis. Although the mouse LGN has neurons with the property of orientation-selectivity, conferred by convergent feed-forward retinogeniculate connections [89], the evidence to be reviewed below places the mechanism for SRP in V1.…”
Section: Stimulus Selective Response Potentiationmentioning
confidence: 99%
“…Given that it occurs in the mouse, SRP offers an opportunity for interventional experimental approaches to test this hypothesis. Although the mouse LGN has neurons with the property of orientation-selectivity, conferred by convergent feed-forward retinogeniculate connections [89], the evidence to be reviewed below places the mechanism for SRP in V1.…”
Section: Stimulus Selective Response Potentiationmentioning
confidence: 99%
“…The presence of DS cells in the LGN raises questions concerning their cortical targets and the potential role in shaping the well-tuned direction/orientation selectivity seen in rabbit/rodent V1 (Piscopo et al 2013;Scholl et al 2013). Previous work (Swadlow and Weyand 1985) showed that LGN DS neurons do project to V1 and that their axons have conduction velocities similar to those of concentric LGN neurons, but the terminal layer of these axons could not be determined with the antidromic methods that were employed.…”
Section: Discussionmentioning
confidence: 99%
“…Orientation preference in cats and primates is columnar and is believed to originate, in part, from selective LGN inputs with ON or OFF receptive field centers precisely aligned with the cortical receptive field subfields (Alonso et al 2001;Hubel and Wiesel 1962;Reid and Alonso 1995;Tanaka 1983; but see Mata and Ringach 2005). By contrast, orientation selectivity in rodents and rabbits is not columnar (Bonin et al 2011;Bousfield 1977;Drager 1975;Girman et al 1999;Metin et al 1988;Ohki et al 2005;Van Hooser et al 2005) and the mechanism(s) generating sharp orientation/direction tuning may differ (e.g., Scholl et al 2013). It is tempting to think that the DS input could contribute significantly to the orientation/directional properties of simple cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these neurons are already contained in the data set published in Scholl et al (2013a). Contrarily to the two other data sets, it is an openly available data set.…”
Section: Lgn Data Setmentioning
confidence: 99%